Propuesta de un sistema de tratamiento de aguas residuales de la industria textil por medio de humedales artificiales (2021)
In this project, the characteristics of the wastewater from the textile industry were known, to which a removal percentage of 90% corresponding to the physicochemical treatment was applied in order to determine which parameters were still above what is indicated by the Resolution 0631 of 2015 for discharges in bodies of water. On the other hand, the types of constructed wetlands were specified according to the following classification: Treatment systems based on emerging rooted macrophytes, Treatment systems based on submerged macrophytes, Treatment systems based on floating leaf macrophytes, Free Flow wetlands (FL) and constructed subsurface flow wetlands, which in turn are subdivided into horizontal and vertical flow.